Role of apelin on oxidative stress in adipocytes - Zhang, Xiaohong (2013)
Adipose tissue, previously considered to be a store of excess energy, is now also regarding as an endocrine organ for its ability to secret various kinds of adipokines that play several roles in key aspects of energy balance, insulin resistance, and hence implicated in metabolic disorders such as obesity and diabetes mellitus. It is generally accepted that obesity increases the risk of developing diabetes. Obesity-induced oxidative stress in adipose tissue can cause dysfunction of adipocytes that link obesity to several diseases including insulin resistance, cardiovascular diseases, and atherosclerosis.